(untitled) (Al-Academy, 2017)
The current study deals with one of the ancient and modern techniques of ceramic art, which has evolved dramatically. This technique is interested in the muddy Body and its coloring, rather than interesting in the coloring of the layer on the surface of the glass port on the ceramic object. It is classified as ceramic techniques of the single heartburn, where use many coloring oxides. As well as, the use of (Pigment), which is often made of metal compounds, or metal oxides such as iron and manganese, copper and cobalt and more others.The first chapter includes the problem, the importance, the goal, and the boundaries of the study. In addition, focuses on determining the terms such as (Sgrafitto). The second chapter consists of two topics, history of the Sgrafitto, and the Sgrafitto’s technique. Additionally, the chapter indicates the theoretical framework. The third chapter, includes the study Procedures, research methodology, the samples and the analysis of the study samples, which consisted of three models of three well-known potters in America; Martin O. Quintana –Sylvian Meschia-Tim Christensen. Finally, in the fourth chapter, the results of the study are listed. The most significant are:The Sgrafitto is a technique that based on the own visions of the potter himself, as it relates to the activities of thinking, feeling and perception. Artist is gaining a tremendous amount of information and experiences through the design and implementation of experimentation, if we take into consideration that this technique depends mainly on the talent and the ability to create and innovate.The dominant element in the structure of the artwork is the (color), as it is one of the means of expression of the feelings and emotions of the artist. He holds the visions and prospects between reality, art, and the environment, which associated color and Material harmonically in the first place. This is what the artist is looking for and looking to achieve. In addition, this increases the importance of the role of color in the main executing various works by the technology of Sgrafitto